A revision of the Fragilaria pectinalis-complex in Europe (Bacillariophyceae, Fragilariaceae) with the description of a new species - van De Vijver, Bart; Kusber, Wolf-Henning; Wetzel, Carlos E.; Williams, David M. (Phytotaxa, 2025)
During routine biomonitoring in Europe, an unknown Fragilaria taxon was frequently observed in western Europe, that was initially identified as Fragilaria pectinalis, a species described in the late eighteenth century from the UK and often misidentified. The epitype material of Conferva pectinalis collected in 1802 by Dillwyn was analysed using both light and scanning electron microscope observations. Additional historic material from the Rabenhorst and Grunow collections was likewise investigated and compared to the unknown French Fragilaria populations identified in Wetzel & Ector (2015) as F. pectinalis. While the Rabenhorst material was identified as F. pectinalis, the taxon described by Grunow as Synedra capitellata f. striis-distantioribus was transferred to the genus Fragilaria and raised to species level. The French populations showed sufficient morphological differences to be separated as a new species, Fragilaria lucectorii, based on valve outline, shape of the apices and stria density. Comparisons are made with similar taxa and brief notes on their ecology are added.